Digital common(s): the role of digital gamification in participatory design for the planning of high-density housing estates - Ng, Provides; Li, Yuechun; Zhu, Shutong; Xu, Bingge; van Ameijde, Jeroen (Frontiers in Virtual Reality, 2023)
‘Digital Commons’ explores the intersection between participatory design, digital gamification, and community engagement, contextualised in the planning of high-density housing estates in Hong Kong. The research project investigates how digital gamified participatory design can be applied in decision-making processes for the planning of public facilities in high-density housing estates. Focusing on community engagement methods, the project has engaged with residents of a case study housing estate, Jat Min Chuen in the Shatin Wai area of Hong Kong, to facilitate collective planning discussions about the past, present, and future of community facilities. Using a digital community game approach, it has collected opinions and needs from public housing residents, promoted collaborative design thinking processes, and provided a platform for participants to increase their understanding of the complexity of planning problems through 3D visualisation tools. The experiences documented in this study demonstrate how 3D interactivity, real-time engagement, and bottom-up perspectives may enhance the potential of using immersive digital twins during collective decision-making. The gaming outcomes show a high similarity across all teams in close relationship to users’ daily life routines, demonstrating a new powerful role for urban designers as a coordinator of interactive and collaborative planning processes.